Hubungan adegan kekerasan di televisi/media sosial dengan perilaku agresif pada anak - Rifa’ah, Hana Meliana (Maliki Interdisciplinary Journal, 2024)
The development of information technology and social media has changed the way children access information and entertainment. With children’s increased exposure to violent content on television and social media, concerns have been raised among parents and communities regarding its negative impact on children’s behavior and character development. Previous research has shown that children who frequently view violent scenes may internalize such behavior as an acceptable norm in social interactions, potentially reducing empathy and increasing aggressive behavior. In this context, it is important to understand the mechanisms underlying the relationship between violent media and aggressive behavior, as well as the factors that influence such exposure. With children spending so much time in front of screens, the challenge for parents to supervise and select appropriate content is growing. Therefore, this study aims to explore the relationship between violent scenes on television and social media with aggressive behavior in children. The results are expected to provide insights to design more effective interventions and policies to protect children from the negative impact of violence in the media.